An Optimization Model for the Maximized Profit of Housing Development Project: A Case Study of Bangkok and Perimeter, Thailand - Siripob Kakaew; Chalida U-tapao (My University, 2023)
The objective of this research was to assess the profitability of the housing development project located in Bangkok, and the perimeter areas are Nonthaburi, Samut Prakan, and Pathum Thani, which are the result of good construction management. Moreover, the researchers’ previous data were used to predict the profit for construction planning, using stepwise multiple regression analysis. Then, we found the profit equation of the housing development project and applied it to the optimization model to clarify the model by the case study. The case study has 427 units, dividing the house into three types, with an optimization performed using the GAMS tool. In the same way, according to this optimization, it can be divided into two scenarios: scenario one found the maximized profit of the project to be 1053.91 MB, and scenario two was the result of making a sensitive analysis of scenario one and found the maximized profit of the project to be 1054.18 MB, which is the best scenario for the maximized profit of the project, and so it is the best choice for construction planning. The research contribution in this model can be applied to other projects that are suitable for large or densely populated cities, such as Beijing, New Delhi, and others. In the Conclusion section, we offer recommendations and detail future work that the researchers have discussed and described for the benefit of future research in housing development projects.
Keywords: BIM and Construction Integration